«Գոթական գրականության» ավանդույթը Էդգար Ալլան Պոյի արձակում - Անի Գալստյան (ՀՀ ԳԱԱ հրատ.)
В этой статье нами были исследованы типичные элементы готической прозы, отраженной в романах Эдгара Аллана По. Мы проанализировали традицию готической прозы, новаторские методы и их дальнейшее влияние на творчество писателя. In this article, the traditional elements of gothic fiction have been taken into consideration. The reflection of these elements in Edgar Allan Poe’s novels has also been shown. The kinds of transformations that these traditional elements of gothic fiction have undergone in Poe’s novels are investigated. How the passive elements have transfigured into active ones in his novels are investigated as well. Besides considering the issues concerning the tradition of gothic fiction, the innovatory creativeness and its further influence on world literature is also considered.
Keywords: Language and Literature